Atlas of zebrafish development - Bryson-Richardson, Robert (Waltham, MA : Academic Press/Elsevier Science, 2012)
Zebrafish are widely considered the best model for vertebrate development. The embryo is transparent, thereby enabling visualization and use of labelling and transgenic approaches. Moreover, because of the ease of inducing new mutations in zebrafish and similarity with the human genome, this organism may be used effectively for disease studies. For example, mutant zebrafish are being utilized for testing drugs that will combat a range of human diseases, from Alzheimer's and cancer to kidney failure and congenital heart disease. For the first time, this atlas provides the research community with a complete reference for zebrafish anatomy spanning the early embryo all the way to adulthood. The authors employ the technique of optical projection tomography (OPT), and offer a series of sections in multiple planes from each sample. The contents are organized by developmental stages, with over 200 images that contain annotations describing anatomical structures relevant to development. In addition, chapters feature explanatory text that highlights major developments in the zebrafish during each stage.